Elite basketball game external load varies between different teams and competition - Ujakovic, F.; Salazar, H.; Pleša, J.; Svilar, L. (Kinesiology, 2024)
Understanding the external load demands of basketball games is fundamental information for training planning and programming. However, there is a scarcity of information about external load during official games at high-level basketball. The purpose of this research was to investigate basketball game external load differences between two elite basketball teams involved in separate competitions. External load demands experienced by forty-six elite basketball players (from two teams) were analyzed using inertial devices during official basketball games. External load was expressed with calculated (PlayerLoad, PL, averaged and in different time epochs) and inertial movement analysis variables (acceleration, deceleration, change of direction and jump). The results showed that the Euroleague team had a higher peak PL in epochs of 30-s (p<.001) and 60-s (p=.02) with moderate and small effect sizes compared to the Eurocup team. The Eurocup team had a significantly higher number of low and moderate accelerations and changes of direction with effect sizes from 0.34 to 1.15. In conclusion, external load demands in basketball vary depending on the team and league therefore practitioners should consider the specific level and style of play when comprising a training plan. Furthermore, practitioners should rely on their own team`s external load values for training load management, rather than attempting to adhere to standards established by external sources.